PERTUMBUHAN DAN PRODUKSI CABAI (CAPSICUM ANNUUM L.) YANG DITANAM DENGAN PEMBERIAN ABU JAJANG SAWIT DAN JENIS MULSA - Husna Yetti; Rusli Yulianter (Jurnal Sagu, 2003)
The research was conducted to evaluate the effect of treatment or addition of oil palm's ash and various kindsmulch on the growth and production of chilli (Capsicum annuum. L). The experimental method used wasrandomized block design method with 2 factor namely 1) Various dosages of oil palm's ash and 2) Variouskinds of mulch. Parameters observed were the height of pLmt, number of primary branchs, number of fruitsper plant and weight offruits per plant The experimental results show that interaction between oil palm's ashand mulch significantly influenced the growth and production of chilli. Addition of ash significantly increa.sedthe number and weight of fruits per plant Treatment with mulch only increased the number of fruit per plant.